Dark-field chest X-ray imaging for the assessment of COVID-19-pneumonia - Manuela Frank; Florian T. Gassert; Theresa Urban; Konstantin Willer; Wolfgang Noichl; Rafael Schick; Manuel Schultheiss; Manuel Viermetz; Bernhard Gleich; Fabio De Marco; Julia Herzen; Thomas Koehler; et al. (Communications Medicine, 2022)
Frank, Gassert et al. use dark-field chest X-ray imaging to assess COVID-19-pneumonia. Dark-field imaging has a higher sensitivity for COVID-19-pneumonia than attenuation-based imaging and provides an ultralow dose alternative to computed tomography imaging for that purpose.